Emerging contaminant degradation of paracetamol using advanced oxidation processes - Napoleão, Daniella Carla; Zaidan, Léa Elias Mendes Carneiro; Salgado, Júlia Barbosa de Almeida; Sales, Renata Vitória de Lima; Silva, Valdinete Lins da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The Emergingcontaminants (EC), considered pollutants persistent and refractory it has been the subject studied worldwide.These compounds are present in different environmental matrices in low concentrations and cause damage to the health of animals and humans, whichmakes alternative treatments may require polishing able to promote its degradation. advanced oxidation processes (AOP) has been applied to this end, so that the present study sought to evaluate the efficiencyof two types of AOP(action UV / H2O2 and photo-Fenton) in EC paracetamol degradation.In order to quantify and detect with reliability, the compound before and after submission to treatments analysis was performed via LC / MS-IT-TOF with a previously validated method. The results showed that the AOPaction UV / H2O2was more efficient achieving promote degradation of paracetamol 100%, which is confirmed by statistical analysis experiments which showed that the addition of free iron (UV / H2O2) were the most effective in drug degradation in aqueous solution. Thus, it is possible to verify that the use of bench reactors with UV-C radiation is effective in paracetamol degradation at a low operating cost.